Geneza utworzenia Uniwersytetu Papieskiego Jana Pawła II w Krakowie - Jan Dyduch (Polonia Sacra)
A weighty event in the history of the theological high school in Cracow was the foundation of the Pontifical University of John Paul II on 19 June 2009, on the Solemnity of the Lord Jesus’ Sacred Heart. It was the Pope Benedict XVI with the Congregation for Catholic Education to carry this out. This important event was preceded by labours aiming at the development of the Pontifical Academy of Theology and by several years’ efforts to transform it into the Pontifical University.